2001
DOI: 10.2307/3871591
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid Activation of Plasma Membrane Ca 2+ Channels in Guard Cells Requires Cytosolic NAD(P)H and Is Differentially Disrupted Upstream and Downstream of Reactive Oxygen Species Production in abi1-1 and abi2-1 Protein Phosphatase 2C Mutants

Abstract: The hormone abscisic acid (ABA) regulates stress responses and developmental processes in plants. Calcium-permeable channels activated by reactive oxygen species (ROS) have been shown recently to function in the ABA signaling network in Arabidopsis guard cells. Here, we report that ABA activation of these I(Ca) Ca(2)+ channels requires the presence of NAD(P)H in the cytosol. The protein phosphatase 2C (PP2C) mutant abi1-1 disrupted ABA activation of I(Ca) channels. Moreover, in abi1-1, ABA did not induce ROS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
313
0
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(338 citation statements)
references
References 22 publications
22
313
0
3
Order By: Relevance
“…We also provide preliminary evidence about ROS production in pollen tubes. In agreement with several others (Pei et al, 2000;Murata et al, 2001;Coelho et al, 2002;Foreman et al, 2003), our studies are consistent with the idea that NAD(P)H is a prime participant. Staining the pollen tubes with CM-H 2 DCFDA reveals that ROS are most concentrated in the region where mitochondria accumulate and also where the NAD(P)H levels are most elevated (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…We also provide preliminary evidence about ROS production in pollen tubes. In agreement with several others (Pei et al, 2000;Murata et al, 2001;Coelho et al, 2002;Foreman et al, 2003), our studies are consistent with the idea that NAD(P)H is a prime participant. Staining the pollen tubes with CM-H 2 DCFDA reveals that ROS are most concentrated in the region where mitochondria accumulate and also where the NAD(P)H levels are most elevated (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, whether H 2 O 2 participates in S1P-induced stomatal closure is still unknown. The results that S1P and H 2 O 2 mediate ABA-induced stomatal closure [5,14,40,41,58] and S1P also reduces stomatal aperture [5,14], this study promoted us to investigate the effect of S1P on H 2 O 2 production in guard cells during darkness-induced stomatal closure. Our results indicated that exogenous S1P induced H 2 O 2 production, and that darkness caused S1P synthesis and H 2 O 2 production.…”
Section: Discussionmentioning
confidence: 82%
“…Nearly all ABA-deficient (aba) and npg ABA-insensitive (abi) mutants exhibit salt insensitivity during germination and are susceptible to drought because of the impaired stomatal aperture regulation (e.g., abi1 and abi2), while plants overexpressing the ABA-response pathway genes, such as SDIR1, ABF3, and ABF4, are tolerant to drought and hypersensitive to salt [33,34,37,38]. ATAF1 overexpression plants showed remarkably enhanced tolerance to drought but were hypersensitive to salt stress.…”
Section: Ataf1 Functions In Aba Signaling and Abiotic Stress Responsesmentioning
confidence: 99%